THU0151 Effects of tofacitinib (CP-690, 550), an oral janus kinase inhibitor, or adalimumab on patient reported outcomes in a phase 3 study of active rheumatoid arthritis. (23rd January 2014) - van Vollenhoven, R.F.; Wallenstein, G.; Lee, E.B.; Fleischmann, R.; Zwillich, S.H.; Gruben, D.; Koncz, T.; Bradley, J.; Wilkinson, B.; Strand, V.
Abstract : Background: Tofacitinib (CP-690, 550) is a novel, oral Janus kinase (JAK) inhibitor being investigated as a targeted immunomodulator and disease-modifying therapy for rheumatoid arthritis (RA). Objectives: To compare the effects of tofacitinib 5 and 10 mg twice daily (BID), and active control adalimumab, with placebo (PBO) on patient reported outcomes (PROs) in patients (pts) with active RA and an inadequate response to methotrexate (MTX). Methods: Pts in this 12-month (Mo), phase 3, randomised control trial (RCT) with RA (≥6 TJC/SJC; ESR >28 mm/h or CRP >7 mg/L) and prior MTX failure were randomised (4:4:4:1:1) to 5 treatment sequences: tofacitinib 5 mg or 10 mg BID; adalimumab 40 mg subcutaneous (SC) injections once every two weeks (Q2W); PBO advanced to tofacitinib 5 mg BID; and PBO advanced to tofacitinib 10 mg BID, all with MTX. Pts on PBO with <20% improvement in TJC and SJC after 3 months were blindly advanced to tofacitinib 5 or 10 mg BID at that time, and all other PBO pts after 6 months. We analysed changes from Baseline to Mo 6 based on the Full Analysis Set (all pts who received ≥1 dose of study drug) using a mixed-effect longitudinal model for the following PROs (secondary endpoints): PtGA [VAS]; pain (VAS); physical function (HAQ-DI); HR-QoL (SF-36); fatigue (FACIT-F), and sleep (MOS Sleep Scale). Results: At Mo 6, treatment with tofacitinib 5 and 10 mg BID, and adalimumab 40 mg Q2W, resulted in statistically significant improvements from baseline vs placebo in all PROs (see Table): Conclusions: In this phase 3 RCT in pts with RA with incomplete responses to MTX, the efficacy of tofacitinib 5 or 10 mg BID in improving PROs was significantly superior to placebo and numerically similar to adalimumab. Disclosure of Interest: R. van Vollenhoven Consultant for: Pfizer Inc, G. Wallenstein Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. B. Lee Consultant for: Pfizer Inc, R. Fleischmann Consultant for: Pfizer Inc, S. Zwillich Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Koncz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Bradley Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, B. Wilkinson Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, V. Strand Consultant for: Pfizer Inc